Neurorecovery after Critical COVID-19 Illness - Alabsi, Haitham; Emerson, Kristi; Lin, David J. (Seminars in Neurology, 2023)
With the hundreds of millions of people worldwide who have been, and continue to be, affected by pandemic coronavirus disease (COVID-19) and its chronic sequelae, strategies to improve recovery and rehabilitation from COVID-19 are critical global public health priorities. Neurologic complications have been associated with acute COVID-19 infection, usually in the setting of critical COVID-19 illness. Neurologic complications are also a core feature of the symptom constellation of long COVID and portend poor outcomes. In this article, we review neurologic complications and their mechanisms in critical COVID-19 illness and long COVID. We focus on parallels with neurologic disease associated with non-COVID critical systemic illness. We conclude with a discussion of how recent findings can guide both neurologists working in post-acute neurologic rehabilitation facilities and policy makers who influence neurologic resource allocation.
Keywords: critical covid illness; covid recovery; long covid; Post-Intensive Care Unit Syndrome; Post-ICU Clinics; neurologic rehabilitation